Repercussions of plagiarism on University degrees in the virtual context: The case of the University of Extremadura - Faba-Pérez, Cristina; Pérez-Pulido, Margarita (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
This article deals with issues related to university plagiarism, students' knowledge of it, and its academic, economic, legal, social, and ethical repercussions. The project covers various university degree courses of the Faculty of Documentation and Communication Sciences of the University of Extremadura. The objective was to analyse the real knowledge that students have about plagiarism and its repercussions, and to verify the students' situation regarding their knowledge of plagiarism, its typology, and its possible consequences. The methodological approach was based on a previous study about the legal and ethical regulations that affect this issue in general and the university environment in particular. Once the analysis of these documents had been carried out, a 17-item Likert-scale questionnaire was prepared which was responded to by a total of 267 students doing different degree courses of the aforementioned Faculty. Simple descriptive statistics were used to analyse the results. They showed that the group with most knowledge about plagiarism and its repercussions was that of the Master's course students (2.27 out of 3). Of the options proposed as a means of identifying plagiarism, that most frequently identified (83.85%) was reproducing a text in a work without citing the author. In general, the questionnaire results indicated that, although the scores were in the top half of the possible values in all cases, they were far from optimal in all of the degree courses analysed. In conclusion, it can be said that plagiarism has become an essential issue throughout the university world, particularly with the use of technology in the academic setting and its problems regarding intellectual property and copyright. The methodology used, applied to the degree courses of the Faculty of Documentation and Communication Sciences of the UEx, allows the context to be analysed, the problem and its causes to be identified, and the imbalances to be corrected, since in many cases students are unaware that they are plagiarising.